Hubungan Indeks Massa Tubuh dengan Tekanan Darah pada Lansia di Wilayah Kerja Puskesmas Kelurahan Cipinang Kecamatan Pulogadung Jakarta Timur - Nugroho, Mochdian Febri; Barkah, Asep (Universitas Malahayati, 2023)
ABSTRACT Today, most people can live into their sixties and beyond. The community health center of cipinang has conducted health services for senior citizens in its working area with 5,242 visits, 1101 visits from senior citizens with overweight BMI, and hypertension is still the most diagnosed disease in elderly services in 2022 with 1650 visits. This study aims to determine